A novel classification of subaxial cervical hemivertebrae and associated surgical management - Wu, Jinhui; Hu, Miao; Tao, Zhengbo; Zhou, Xin; Jiang, Heng; Lin, Tao; Ma, Jun; Gao, Rui; Wang, Ce; Zhou, Xuhui (Frontiers in Surgery, 2023)
Objective: To propose and validate a new classification of surgical methods for patients with subaxial cervical hemivertebrae. Method: This article reviewed cases diagnosed with subaxial cervical hemivertebrae in our hospital from January 2008 to December 2019. The results of preoperative (initial visit), postoperative and/or final follow-up were assessed using the Japanese Orthopaedic Association (JOA) score, Neck Disability Index (NDI) score, spinal balance parameters, and Scoliosis Research Society-22 Questionnaire (SRS-22). We also performed a reliability study to assess this classification. Result: The classification includes three types. Each type can be divided into two subtypes, and a preliminary algorithm is proposed. Type I: There is an obvious appearance deformity in the neck, there are hemivertebrae in the cervical spine, and only a single hemivertebra of the subaxial cervical hemivertebra needs to be resected. Type II: There is an obvious appearance deformity in the neck, there are hemivertebrae in the cervical spine, and multiple subaxial cervical hemivertebrae need to be removed. Type III: No apparent deformity in the neck, at least one subaxial cervical hemivertebra existed or Klipper-Feil syndrome. Each type is divided into two subtypes, A and B, according to whether the upper and lower adjacent vertebral bodies of the rescected hemivertebra(e) are fused. We propose corresponding treatment methods for different types. We included a total of 121 patients and reviewed the prognosis for each type of patient. All patients achieved satisfactory results. The reliability study showed that the mean interobserver agreement was 91.8% (89.3%-93.4%), and the κ value was 0.845 (0.800-0.875). The intraobserver agreement ranged from 93.4% to 97.5%, with a mean κ value of 0.929 (0.881 to 0.954). Conclusion: In our study, we proposed and validated a new classification of subaxial cervical hemivertebrae and proposed corresponding treatment plans for different classifications.